Низкоразмерные кристаллы кремния для фотоэлектрических преобразователей - Druzhinin, A. A.; Ostrovskii, I. P.; Khoverko, Yu. N.; Nichkalo, S. I.; Berezhanskii, Ye. I. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The possibility of using of silicon nanowires ensembles as an anti-reflective surface for silicon photovoltaic cells is shown. The technological process for nanoscale anti-reflective surface is developed, the structures of silicon photovoltaic cell are examined and their characteristics are studied.